Reservoirs: mirrors of the surrounding landscape? - Geraldes, Ana Maria (2010)
To assess in what extent the environmental quality of aquatic systems reflect landscape features several water quality parameters were determined in two reservoirs. Concomitantly, the surrounding landscape was characterized and the existing potential sources of phosphorous and nitrogen runoff were identified and when possible estimated.